Transportation Inequalities for Multivalued Stochastic Evolution Equations (Journal of Partial Differential Equations, 2017)
" In this paper, using the Girsanov transformation argument, we establish Talagrand-type T_2 inequalities under the d_2 metric and the uniform metric d_\u221e for the law of the solution of a class multivalued stochastic evolution equations."
Keywords: Transportation cost inequalities; Girsanov transformation; multivalued stochastic evolution equation